CORRELATION BETWEEN PERSONAL HYGIENE AND INFECTION OF INTESTINAL HELMINTHS AMONG STUDENTS AT THE PUBLIC ELEMENTARY SCHOOL 3 ABELI, KENDARI INDONESIA - Anita Rosanty (Public Health of Indonesia)
Backgrounds: Intestinal helminth is one of diseases derived from environment and still becomes a helath problem in Indonesia until today. The high number of intestinal helminth prevalence in Indonesia is related with bad personal hygiene, including handwashing habit, nail hygiene, and foot-wear wearing habit.